Pratiques de gestion et rapports d’âge en milieu de travail - Yolande Pelchat; André Campeau; Julie Bradette; Michel Vézina (Perspectives Interdisciplinaires sur le Travail et la Santé)
The aging workforce and its potential consequences are causes for concern. To date, planners, like researchers in various disciplines, have tended to merge this issue with the increased presence of older or aging workers - two adjectives that are generally used to describe workers aged 45 or older - in workplaces. During an exploratory study conducted within the Quebec public service, we decided to follow an entirely different path by examining how various actors in workplaces (employees and managers) construct and deconstruct age identities. The analysis shows direct links between these identities and work organization, more specifically management practices. The results suggest that relationships among employees of different ages, as well as the characteristics they assign to each other, are constructed during management practices. They prompt the review of the a priori of an "intergenerational gap" that already exists in society and that turns the workplace into a place where this gap is simply expressed.